The inn of the sixth happiness [videorecording (DVD)] - Robson, Mark, 1913-1978; Bergman, Ingrid, 1915-1982; Donat, Robert, 1905-1958; Jürgens, Curd, 1915-1982; Burgess, Alan (20th Century Fox, 2003)
Based on the true-life story of Gladys Aylward, an English missionary that led a group of children through war-torn China in the 1930's. Nominated for an Academy Award, Best Director.